Assessment of Knowledge, Attitude, and Practices of Personal Protective Equipment among Health Care Providers in Tamil Nadu, South India - Lavanya, Dominic Savio; Sony, Paul; Kannan, Iyanar; Thenmozhivalli, PR (International Journal of Occupational Safety and Health, 2023)
Introduction: Personal protective equipment provides considerable protection from hospital-acquired infections. Ample knowledge with a positive attitude and best practices of personal protective equipment by healthcare workers is indispensable to get protection themselves and to serve humanity. The study aimed to assess the knowledge, attitude, and practice (KAP) regarding personal protective equipment (PPE) among healthcare workers along with possible determinant factors. Methods: An observational cross-sectional study was conducted from August - September 2022 among 386 healthcare workers in Tamil Nadu, South India. The structured self-administered questionnaire was used for data collection. The study comprised questions evaluating a socio-demographic profile, knowledge, attitude, and practice of personal protective equipment. Descriptive statistics (percentage, frequency, mean) and inferential statistics (Chi-square test) were used for the data analysis. Results: The overall knowledge of the participants was satisfactory (73.3%). Physicians had a good knowledge level against non-physicians (p<0.05). It was observed that the 30 and more years of experience group has less knowledge (p<0.05). A positive attitude toward PPE was noted in 58.3% of the participants. Statistical significance in the attitude of participants with education, occupation, and experience was not observed (p>0.05). Good practice of PPE was followed by 66.8% of participants. Nurses(91.7%) showed good practice of PPE than physicians and laboratory technicians and was found to be statistically significant (p<0.05). Conclusion: The findings demonstrated that most healthcare workers had an overall good knowledge, positive attitude, and good practice regarding PPE however they need periodical training and auditing.